CHARACTERISTIC AND RUBBER PLANT REVEGETATION AT THE POST COAL MINING LAND KUTAI KARTANEGARA REGENCY - ., SUJIMAN; SITORUS, SANTUN R.P.; OKTAVIANI, R.; ., MACHFUD (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2011)
The research objective was to analyse the characteristic of post coal mining land in Kutai Kartanegara Regency and to find out what commodities that suitable for vegetation of this land. The methode of research was using primary data including soil sampling taken with purposive sampling and composite methode. Rubber planting experiment was also carried out at two different soil conditions, that was land with original soil and land withtailing soil (overburden of coal mining). Both soil conditions were employed experimental using randomized completely block design with four treatments, i.e. : (1) without fertilizer, (2) liming, (3) manure fertilizer, and (4) manure fertilizer + liming. Secondary data for commodity research was taken from bureau of statistic centre, labour service, and mining service of Kutai Kartanegara Regency.The result showed that reclaimed land (5-20 years) was classified as S2 class of land suitability for rubber. The competitive commodities of Kutai Kartanegara Regency were rubber, coffea, and coconut, meanwhile strategic commodities were oil palm, pepper, and cocoa. The result of rubber experiment showed that post coal mining land with original soil significantly affective to leaf amount, height, and stem diameter of rubber.